Patient-reported outcome measures in the management of neovascular age-related macular degeneration: a 1-year prospective study. Issue 1 (3rd October 2019) - Jelin, Elma; Wisløff, Torbjørn; Jørstad, Øystein Kalsnes; Heiberg, Turid; Moe, Morten Carstens
Abstract : Objective: To prospectively explore the following patient-reported outcome measures (PROMs) in the management of neovascular age-related macular degeneration (nAMD): (1) self-reported visual function, (2) symptom-state, (3) general-health and (4) satisfaction of treatment. Methods and analysis: Corresponding to the four PROMs, participants responded to the following questionnaires: (1) National Eye Institute Visual-Functioning-Questionnaire (NEI-VFQ-25), (2) Patient-Acceptable-Symptom-Status (PASS 5), (3) EuroQol-Group-Questionnaire (EQ-5D-3L) and (4) Dimensions of Importance in Treatment of nAMD (DITAMD). Data were collected at baseline and after 3, 6 and 12 months of intravitreal antivascular endothelial growth factor treatment. Results were evaluated with t-tests and mixed linear regression analyses. Results: The study included 197 patients. At baseline NEI-VFQ-25 (79.53±14.52) and EQ-5D (0.74±0.28) had relatively high scores, whereas PASS 5 was below 'acceptable' (3.30±0.80). At 12 months NEI-VFQ-25 and PASS 5 showed significant improvement, whereas EQ-5D and DITAMD remained unchanged. At baseline patients receiving treatment of the better-seeing eye (BSE) (n=52) reported significantly worse NEI-VFQ-25 and PASS 5 than patients for whom treatment only involved the worse-seeing eye (WSE), (n=145). In contrast to BSE patients, there was no improvement of NEI-VFQ-25 for WSE patients at 12 months, despite a significant improvement in best-corrected visual acuity (BCVA). Two independent variables, treatment including the BSE and BCVA for the treated eye, were found to predict both NEI-VFQ-25 and PASS 5. Conclusion: After 12 months of nAMD treatment, there was a significant improvement in PASS 5 and NEI-VFQ-25, the latter depending on whether therapy included BSE. EQ-5D and DITAMD remained unaltered.